An information exchange framework between physical modeling and numerical simulation to advance tropical cyclone boundary layer predictions. Issue 143 (August 2015) - Tse, K.T.; Li, S.W.; Fung, J.C.H.; Chan, P.W.
Abstract: Our previous findings (Tse et al., 2014 ) suggest that both the physical and numerical simulations of a tropical cyclone boundary layer can be improved by information exchanges. In the present study, the improvements are quantitatively measured. For one thing, the approaching wind flow adopted in a wind-tunnel topographic study is adjusted according to the mean wind profile extracted from a meso-scale meteorological simulation of Typhoon Fengshen (2008) for a particular period, during which the observed wind direction indicated the sea-fetch wind flow. For another thing, the measurements obtained in a wind-tunnel topographic study are processed and used to improve the meso-scale meteorological simulation through observation nudging. Comparisons with the field-measurements taken at a main weather station and several auxiliary weather stations reveal that both the numerical and the physical simulations are improved. Specifically, the super-gradient flow—observed at the weather stations but not in the conventional wind-tunnel topographic study—is successfully simulated in the improved wind-tunnel test. The wind tunnel measurements, which more accurately reflect the influence of the underlying terrain, are incorporated into the meso-scale meteorological simulation of Typhoon Fengshen (2008). The simulation yields the results in better agreement with the field-measurements of the relative strength of wind speeds, with the exception of the wind strengths at mountain-summit points.